Alternative care options and social protection policy choices to support orphans and vulnerable children : a comparative study of Mozambique and Guinea-Bissau - Shibuya, Tomoko (Department of Social Development, 2016)
The number of orphans in Sub-Saharan Africa reached 51,900,000 in 2013. There has been limited research, particularly in the countries of Mozambique and Guinea-Bissau, on the role of social protection policies, types of alternative care, and fulfillment of basic needsin ensuring the welfare of this vulnerable population. The goal of the present thesis was to examine the interconnections between these factors and their relations to the overall well-being of 122 orphans and vulnerable children between the ages of 10 and 17 yearsin the two countries. Using a mixed-method approach, both quantitative data (health, basic needs fulfillment, domains of well-being) and exploratory qualitative interview-based data were collected. A literature review on the social protection policies of orphans and vulnerable children (OVC) was undertaken prior to data collection in the field. Caregivers and local authorities were also interviewed. The results showed a marked difference in the way basic and psycho-social needs were met in the different types of alternative care situations children experienced in the two countries. The well-being of children varied widely among the care centres within each country, and indicated a comparative advantage for those children living in residential centres. The findings also indicated that the efforts to support orphans and vulnerable children were more advanced in Mozambique than in Guinea-Bissau at the policy-level, but this did not necessarily translate into higher overall well-being for children in that country. Significant associations were also found between the overall well-being of orphans and vulerable children and their social situation in the community, food, health, and education situations. Taking these findings into account, the researcher calls for more comprehensive social protection policies in the two countries, promoting community integration of these children.